KEAMANAN DATA DALAM SISTEM DATABASE - Annisa Hafsah; Aininta Alivia Br. Kaban; Said Luthfi Ramadhan; Nurbaiti Nurbaiti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The rapid development of information technology has encouraged various organizations to implement database-based management information systems (MIS) as a means of increasing operational efficiency and the quality of decision making. However, dependence on this system also increases vulnerability to data security disturbances, both from external parties such as cyber attacks and malicious software, as well as from internal parties through misuse of access rights. This research aims to analyze the effectiveness of implementing data protection mechanisms in management database systems using a literature study and case study approach. The research focus includes evaluation of encryption systems, role-based access control (RBAC), as well as threat detection and response systems in maintaining aspects of confidentiality, integrity and data availability. Simulations were carried out on two database management systems, namely MySQL and PostgreSQL, to assess how effective security features are in responding to attacks and their impact on system performance. The research results show that with proper security implementation, organizations can improve data protection without sacrificing system performance. In addition, this study emphasizes the important role of organizational awareness of information security as well as the need for internal regulations such as security training and implementing strong authentication. It is hoped that these findings will provide benefits both conceptually and practically for strengthening safe and reliable information systems in the organizational environment.